Analisis Kesiapan Pemerintah Kota Banjarmasin Menuju Kota Cerdas - Ika Sartika (Post Graduate School of Government Science, 2023)
The city of Banjarmasin is included in the 100 Smart City program launched by the Ministry of Information and Communication. Given the unique geographical conditions with many rivers, the concept of smart city development in Banjarmasin can be different from other cities. Of course the Banjarmasin City government must be truly ready to realize a smart city according to geographical conditions and be able to improve public services. The newly launched Banjarmasin Smart City still requires improvement, related to application integration and the level of utility and effectiveness which is still relatively low. This study aims to analyze the readiness of the Banjarmasin City Government towards a smart city, which is followed by identifying factors that can accelerate the formation of a smart city in Banjarmasin City. The method used is descriptive quantitative and qualitative. Quantitative data analysis uses descriptive statistics with visualization of radar diagrams. While the qualitative data analysis used the NVIVO 12 PLUS software to map the results of interviews with informants, then the coding process was carried out from the interview results to each node based on the dimensions of a smart city. The results of the study concluded that the readiness of the Banjarmasin City Government towards a smart city is in the ready (middle) category towards being ready and able to compete (main). Factors that can accelerate the realization of Banjarmasin Smart City are: integrated data center, conducive business climate, health, environmentally friendly urban planning, fair and consistent application of reward and punishment, critical and cultured society, mixed modes of transportation, and adequate physical and internet infrastructure. Meanwhile, the smart community dimension has the greatest contribution to realizing Banjarmasin Smart City.